Production and Evaluation of Mexican-Style Chorizo Sausage Using Invasive Silver Carp (Hypophthalmichthys molitrix) Meat. Issue 5 (28th May 2019) - Trindade, M.A.; King, J.L.; Liceaga, A.M.
ABSTRACT: In the United States, silver carp ( Hypophthalmichthys molitrix ) is classified as an invasive fish with no commercial value. The main objective of this study was to develop a Mexican-style fish chorizo sausage with silver carp meat. Four formulations (1) containing vinegar (Wet); (2) Wet plus canola oil (O) and cassava starch/soy protein isolate extenders (E); (3) dry seasoning with no vinegar (Dry); and 4) Dry plus OE were evaluated for physicochemical characteristics (proximate composition, pH value, color, cook loss, and textural hardness) and sensory acceptability using 9-point hedonic and just-about-right scales. The addition of OE did not increase (P > 0.05) physicochemical characteristics nor (P > 0.05) sensory acceptance of the chorizo. In contrast, use of DS increased (P > 0.05) the sensory acceptability. However, panelists indicated a "saltiness" perception in all four formulations. A fifth formulation was processed using DS without salt addition. Sensory acceptability increased for this new formulation (scores between 7, like moderately, and 8, like very much). In conclusion, it is possible to formulate a Mexican-style fish chorizo sausage using silver carp meat with DS and no salt. Fish chorizo has good physicochemical characteristics and sensory acceptance, demonstrating a good alternative use for this otherwise underutilized invasive fish species.